Counterculture and Moral Panic in Anand Neelakantan’s Asura: Tale of the Vanquished (International Journal of Food and Nutritional Sciences, 2022)
Anand Neelakantan is a renowned author of twenty-first century who has deconstructed mythology. In Asura: Tale of the Vanquished, he has shifted the narrative from deified Rama and demonic Ravana to Lord Rama and humane Ravana. Rama is a Deva who strictly adheres to the caste system and Ravana is an Asura who seeks to build a utopian kingdom. The cultural identity between the two races contradicts each other. They view each other as a threat to their tradition. Both the races have their own concept of righteousness and moral codes to justify their deeds. They are perceived as counterculture from each other’s perception as they see other culture as unorthodox and outlandish. This paper aims to articulate the difference in cultural traditions followed by both the races which further catalyses moral panic between the races.